Pitsimpurnko aphēgēma - Triantaphyllu, Sōtē 1957- (Ekdoseis Patakē, 2023)
"This short book "written in letter form" is the story of Demosthenes and Elegos, a newly married couple from Chios. Demosthenes has immigrated to Pittsburgh, Pennsylvania, while his young wife waits on the island for the coveted ferry ticket to meet him in America. Through the correspondence of Demosthenes and Elegos – dating back to the days of the First World War – fragments of the migratory experience in the steel and coal landscapes, as well as the history of Chios, are recorded. "Pitsimburgo" is a shattered dream; A lost detail of the great adventure of migration."--
Originally published, 2006
In griechischer Schrift
Keywords: Geschichte 1913-1914; Griechischer Einwanderer; Chios; Pittsburgh, Pa.; Greeks / Pennsylvania / Pittsburgh / Fiction; Immigrants / Pennsylvania / Pittsburgh / Fiction; Pittsburgh (Pa.) / Emigration and immigration / Fiction; Chios (Greece : Municipality) / Emigration and immigration / Fiction; Grecs / Pennsylvanie / Pittsburgh / Romans, nouvelles, etc; Chio (Grèce : Île) / Émigration et immigration / Romans, nouvelles, etc; Fiktionale Darstellung